Influência do molibdênio e do nitrogênio sobre duas variedades de feijão - de Andrade Araújo , Geraldo A; Nogueira Fontes , Luiz Antônio; do Amaral, Flávio A L; Condé, Alcides R (Revista Ceres, 2025)
The effect of three levels of nitrogen (30, 60, and 90 kg/ha) and three levels of molybdenum (10, 20, and 30 g/ha) on the dry bean varieties ‘Rico-23’ and ‘I-162 Guatemala’ was studied in Viçosa Minas Gerais State.